Pendidikan Kesehatan Reproduksi dan Gizi Seimbang (Pk-Rgs) Meningkatkan Pengetahuan dan Sikap Remaja Putri dalam Mencegah Stunting - Rosiana, Nisa; Wuriningsih, Apriliani Yulianti; Rahayu, Tutik (Pustaka Galeri Mandiri, 2025)
Stunting was a condition in which a child's growth was slowed due to malnutrition or frequent infections, leaving them at high risk of disease and death. There study was a quasi-experimental study using quantitative methods and a control group approach with pre-test and post-test. Data collection was conducted using a questionnaire. A total of 37 respondents were selected using a stratified sampling technique. The data obtained were statistically analyzed using the paired t-test and independent t-test formulas. Based on the analysis, the majority of 37 respondents (73%) were 17 years old and over. Furthermore, 91.9% of respondents had high knowledge of stunting prevention, while 8.1% had moderate knowledge of reproductive health. All respondents, or 100% of respondents, had positive attitudes toward stunting prevention. There was a difference in knowledge and attitudes among adolescent girls regarding stunting prevention before and after receiving reproductive health and balanced nutrition education at Sultan Agung 1 Islamic High School in Semarang. This was demonstrated by a p-value of 0.000 < 0.05.